Modeling and Forecasting the Dynamics of BRICS Socioeconomic Integration in Context of Global Economic Fragmentation - Pessoa, Gustavo; Vlasova, Yulia; Shkalenko, Anna; Kaldibayev, Nurlan; Ponkratov, Vadim; Kuznetsov, Nikolay; Elyakova, Izabella; Bloshenko, Tatiana; Kireeva, Elena; Romanenko, Elena (Ital Publication, 2025)
This research aims to model and forecast the trajectory of socioeconomic integration between the BRICS countries and Turkey in the context of deglobalization and escalating geoeconomic fragmentation. The study evaluates the impact of external shocks, including the updated US tariff regime, trade conflicts, global downturns, sanctions pressure, and institutional limitations, on the sustainability and intensity of intra-bloc engagement. Employing a comparable panel time series from 2000 to 2023 for a selected set of countries, we apply several econometric methods for the first time in a unified framework: panel ARDL, Dumitrescu-Hurlin panel Granger causality tests, impulse response functions, variance decomposition, and ARIMA forecasting up to 2030. The empirical analysis results show that regional financial integration, infrastructure development, and R&D have a statistically significant and persistently positive impact on intra-bloc trade volumes and socioeconomic cooperation between BRICS countries and Turkey. Simultaneously, digital connectivity shows a short-term stimulating effect followed by phase saturation, indicating the need for the structural modernization of the digital environment. Institutional attributes exhibit heterogeneous effects, underscoring the necessity of harmonizing regulatory frameworks and aligning them with international sustainable development standards. The scientific novelty of this study resides in the design and empirical validation of an advanced forecasting model that incorporates institutional, infrastructural, innovation-related, and digital dimensions. This study delineates integration scenarios for BRICS and Turkey intended to inform strategies for regional macroeconomic coordination, establish transaction mechanisms based on national currencies, and define balanced investment priorities within the transition toward a multipolar global governance architecture.